2015
DOI: 10.1016/j.pharmthera.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective peptides fused to arginine-rich cell penetrating peptides: Neuroprotective mechanism likely mediated by peptide endocytic properties

Abstract: Several recent studies have demonstrated that TAT and other arginine-rich cell penetrating peptides (CPPs) have intrinsic neuroprotective properties in their own right. Examples, we have demonstrated that in addition to TAT, poly-arginine peptides (R8 to R18; containing 8-18 arginine residues) as well as some other arginine-rich peptides are neuroprotective in vitro (in neurons exposed to glutamic acid excitotoxicity and oxygen glucose deprivation) and in the case of R9 in vivo (after permanent middle cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 140 publications
5
79
0
1
Order By: Relevance
“…Meloni et al . also reported that increasing poly-arginine length increased their biological activity 37 . However, in the case of oligoarginine peptide-modified EVs, the gathering of oligoarginine peptides on EVs as scaffolds affects their functionality of cellular uptake and cytosolic release efficacy.…”
Section: Discussionmentioning
confidence: 95%
“…Meloni et al . also reported that increasing poly-arginine length increased their biological activity 37 . However, in the case of oligoarginine peptide-modified EVs, the gathering of oligoarginine peptides on EVs as scaffolds affects their functionality of cellular uptake and cytosolic release efficacy.…”
Section: Discussionmentioning
confidence: 95%
“…In brief: secondary ion micrographs were acquired using the CAMECA NanoSIMS 13 structure, (ii) 13 C content and (iii) Ca and Fe distributions. For (i) and (ii), a Cs + primary ion beam (nominal beam diameter = 100 nm, current = 1.5 pA) was used to sputter the negative ion species 12 C 12 C -, 12 C 14 N -, 31 P -, 32 S -, 35 Cl -and secondary electrons (for structural information), as well as 12 C -, 12 C 12 C -, 13 C 12 C -, 12 C 14 N -, 31 P -and secondary electrons (for 13 C isotopic information). For (iii), an O -primary ion beam (nominal beam diameter = 600 nm, current = 28 pA) was then used to sputter the positive ion species 12 C + , 23 Na + , 40 and elemental symbol (Ca), not oxidation state (e.g.…”
Section: In Vivo Assessments Of Effects Of Npmentioning
confidence: 99%
“…Here we use an in vitro model of injury to the CNS, and demonstrate similar increases in AQP4 in mixed retinal cells. Glutamate is added to the cultures to simulate the glutamate excitotoxicity that occurs following injury to neurons and supporting glia 35 resulting in increased AQP4 immunoreactivity.…”
mentioning
confidence: 99%
“…In addition, arginine-rich peptides were shown to be neuroprotective in a rat stroke model and also capable of reducing neuronal calcium influx following glutamate excitotoxicity [11]. Finally, mounting evidence suggests that the neuroprotective actions of TAT-fused neuroprotective peptides is largely mediated by the arginine residues and to a lesser extent lysine and tryptophan residues within the TAT and/or cargo peptide [12].…”
Section: Expert Review Of Neurotherapeuticsmentioning
confidence: 99%
“…Rather, it has been proposed that at least one mechanism by which these arginine-rich peptides exert their neuroprotective effects is by inducing the internalization of neuronal cell surface structures, as a result of endocytosis [10,12,13], thereby reducing the effects of excitotoxicity and its down-stream neuro-damaging signaling pathways. Additionally, poly-arginine and other cationic arginine-rich peptides are potent inhibitors of proprotein convertase enzymes, including furin [14], a ubiquitously expressed calcium-dependent convertase involved in both physiological and pathological processes such as matrix metalloproteinase activation.…”
Section: Expert Review Of Neurotherapeuticsmentioning
confidence: 99%